A proposal for design of 2 – 4 GHz wideband bandpass filter using suspended substrate stripline for passive radar systems - Trieu Van Diep; Bui Thi Hang (Journal of Military Science and Technology, 2024)
This article proposes a solution to design of front-end bandpass filters which finds application in wideband receivers for passive radar systems. The structure employs suspended substrate stripline as base transmission lines, dual-frequency resonators, and broad-side coupling patterns to render a wideband, steep cutoff and low-loss bandpass filter that aims at replacing lossy microstrip-based or bulky waveguide-based filters. The structure is able to scale to different operating frequency ranges in electronic warfare systems.